2015
DOI: 10.1016/j.jneuroim.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy reduces infarct volume and neuroinflammation in male but not female mice in experimental stroke

Abstract: The peripheral immune response contributes to neurodegeneration after stroke yet little is known about how this process differs between males and females. The current study demonstrates that splenectomy prior to experimental stroke eliminates sex differences in infarct volume and activated brain monocytes/microglia. In the periphery of both sexes, activated T cells correlate directly with stroke outcome while monocytes are reduced by splenectomy only in males. This study provides new information about the sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 37 publications
2
80
0
Order By: Relevance
“…Accordingly, reduced CD45 hi /CD11b + cells (activated microglia and infiltrated macrophages) in the brain and fewer spleen contractions have been related to the smaller injury in females [166]. Splenectomy was effective in reducing the injury size and CD45 hi /CD11b + cells in the ischemic brain only in male mice, supporting a role for peripheral mononuclear phagocytes to the sex differences in stroke [88]. While most stroke studies exclude female animals owing to the hormonal changes with the estrus cycle, evidence suggests sex as an important biological variable to be addressed in stroke research.…”
Section: Sex-associated Modulation Of Mononuclear Phagocytesmentioning
confidence: 86%
See 2 more Smart Citations
“…Accordingly, reduced CD45 hi /CD11b + cells (activated microglia and infiltrated macrophages) in the brain and fewer spleen contractions have been related to the smaller injury in females [166]. Splenectomy was effective in reducing the injury size and CD45 hi /CD11b + cells in the ischemic brain only in male mice, supporting a role for peripheral mononuclear phagocytes to the sex differences in stroke [88]. While most stroke studies exclude female animals owing to the hormonal changes with the estrus cycle, evidence suggests sex as an important biological variable to be addressed in stroke research.…”
Section: Sex-associated Modulation Of Mononuclear Phagocytesmentioning
confidence: 86%
“…Increased apoptosis in the spleen, albeit controversial (see Kim et al [25]), and cell release from the spleen are related to reduced spleen size [26]. Others have also reported that splenectomy or splenic irradiation reduces ischemic injury in animal models of stroke [87][88][89]. While these data provided a rationale for targeting the spleen as a therapeutic strategy for patients with stroke, there are reports that argue against this approach.…”
Section: Monocytes and Monocyte-derived Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune response to stroke differs between males and females. For instance, male mice exhibit an initial increase in infarction characterized by an early and more robust recruitment of CD45 high CD11b+ macrophages into post-ischemic brain relative to females (Banerjee et al 2013; Dotson et al 2015). If the spleen is removed prior to MCAO, sex differences in infarct and activated microglia/macrophages in the brain is lost due to, in part, a decrease of peripheral CD11b+ cells in males only (Dotson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of splenocytes after stroke leads to a release of leukocytes into the periphery, followed by infiltration of pathogenic immune cells into the brain and activation of microglial cells, which exacerbate ischemic injury [710]. Rodents that are splenectomized prior to middle cerebral artery occlusion (MCAO) exhibit a decrease in infarct volume, associated with reduced inflammatory leukocytes and pro-inflammatory cytokines in the ischemic brain [4, 11]. Additionally, when spleens were irradiated 4 h after MCAO, infarct volume, microglia and infiltrating T cells in the ischemic brain were reduced, presumably due to inhibition of splenocyte efflux [12].…”
Section: Introductionmentioning
confidence: 99%